2013
DOI: 10.1038/jcbfm.2013.226
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban Does Not Increase Hemorrhage after Thrombolysis in Experimental Ischemic Stroke

Abstract: The management of acute ischemic stroke during anticoagulation with a novel oral anticoagulant (NOAC) is challenging because intravenous thrombolysis is contraindicated because of a putative increased risk of intracerebral hemorrhagic complications. We examined the risk of secondary postischemic hemorrhage after thrombolysis in rodents pretreated with rivaroxaban or warfarin. Mice were pretreated with either rivaroxaban (30 mg/kg), warfarin (target international normalized ratio 2 to 3) or vehicle. After 2 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 43 publications
6
31
1
Order By: Relevance
“…In experimental studies, pretreatment with dabigatran or rivaroxaban did not increase the rate of thrombolysis-associated ICH. 72,73 Data on the safety and efficacy of intravenous thrombolysis in AIS patients receiving NOACs are limited to approximately 2 dozen case reports and a retrospective multicenter cohort study. Among the case reports, ICH and poor outcome were rarely reported when recombinant tissue-type plasminogen activator was administered minutes to 24 hours after the last anticoagulant dose.…”
Section: Management Of Patients On Noacs Who Are At Risk For Bleedingmentioning
confidence: 99%
“…In experimental studies, pretreatment with dabigatran or rivaroxaban did not increase the rate of thrombolysis-associated ICH. 72,73 Data on the safety and efficacy of intravenous thrombolysis in AIS patients receiving NOACs are limited to approximately 2 dozen case reports and a retrospective multicenter cohort study. Among the case reports, ICH and poor outcome were rarely reported when recombinant tissue-type plasminogen activator was administered minutes to 24 hours after the last anticoagulant dose.…”
Section: Management Of Patients On Noacs Who Are At Risk For Bleedingmentioning
confidence: 99%
“…8,9 The knowledge about IVT in NOAC patients is limited and based on case reports. [14][15][16][17][18]20,21,24 Data from animal models showed no excessive risk of ICH after IVT in rodents with a prior treatment with rivaroxaban, 43,44 dabigatran, 45,46 and apixaban 44 in comparison with VKA. Currently, the use of IVT for acute ischemic stroke in patients with a recent (<48 hours) intake of a NOAC is regarded off-label.…”
Section: Discussionmentioning
confidence: 99%
“…In another experimental study led by the same group, reversion of VKA effects by prothrombin complex concentrates eliminated the excess risk of bleeding after rtPA use [20]. Similar experiments conducted with apixaban showed that the risk of haemorrhagic transformation was lower with DOACs than with VKAs after thrombolysis [21,22].…”
Section: Experimental Data On Thrombolysis On Doacsmentioning
confidence: 95%